CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel